Gender Differences in Clinical and Psychosocial Features Among Persons With Schizophrenia: A Mini Review - Giordano, Giulia Maria; Bucci, Paola; Mucci, Armida; Pezzella, Pasquale; Galderisi, Silvana (Frontiers in Psychiatry, 2021)
An extensive literature regarding gender differences relevant to several aspects of schizophrenia is nowadays available. It includes some robust findings as well as some inconsistencies. In the present review, we summarize the literature on gender differences in schizophrenia relevant to clinical and social outcome as well as their determinants, focusing on clinical variables, while gender differences on biological factors which may have an impact on the outcome of the disorder were not included herewith. Consistent findings include, in male with respect to female patients, an earlier age of illness onset limited to early- and middle-onset schizophrenia, a worse premorbid functioning, a greater severity of negative symptoms, a lower severity of affective symptoms and a higher rate of comorbid alcohol/substance abuse. Discrepant findings have been reported on gender differences in positive symptoms and in social and non social cognition, as well as in functional outcome and rates of recovery. In fact, despite the overall finding of a more severe clinical picture in males, this does not seem to translate into a worse outcome. From the recent literature emerges that, althoug some findings on gender differences in schizophrenia are consistent, there are still aspects of clinical and functional outcome which need clarification by means of further studies taking into account several methodological issues.